INTEGRATION OF INFORMATION SYSTEMS IN ENTERPRISE MANAGEMENT BASED ON DIGITALIZATION (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2024)
This article explores the integration of information systems in enterprise management within the context of digitalization. It addresses the challenges and benefits associated with implementing digital solutions in modern enterprises and examines how digital transformation fosters improved efficiency, decision-making, and overall organizational performance. The study analyzes literature on the subject and presents methods for effective system integration. The results section highlights successful case studies, while the discussion focuses on the implications for future enterprise management strategies. The paper concludes with actionable recommendations for organizations aiming to enhance their digital maturity.